Conductive copper paste for microwave dielectric ceramic metallization and preparation method and application thereof

CN122968034APending Publication Date: 2026-10-23SHENZHEN BAROY NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611255154.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,尽管铜浆优势明显,但铜元素在高温环境下极易氧化,导致其在高温共烧过程中的可靠性不足

Benefits of technology

[0017]本发明的技术方案通过在导电铜浆原料中引入了经Q值调节剂改性的玻璃粉与烧结助剂。一方面,改性玻璃粉在高温下能软化浸润基材,促进形成高致密度的烧结铜膜,并通过调整介电常数匹配度减少信号损耗,提升微波器件品质因数。另一方面,烧结助剂不仅能降低烧结温度、抑制晶粒过度长大,其活性组分还能原位去除铜表面氧化膜,改善界面润湿性并加速物质迁移,促使金属界面实现充分的晶间或晶内结合。两者通过互联助熔作用,不仅大幅提升了烧结铜膜的致密度,还显著增强了铜层与基材的附着力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses conductive copper paste for microwave dielectric ceramic metallization and a preparation method and application thereof, and relates to the technical field of electronic materials.The raw materials of the conductive copper paste for microwave dielectric ceramic metallization include conductive copper powder, modified glass powder, an organic carrier, a dispersing agent and a sintering aid.The raw materials of the modified glass powder include a glass base and a Q value adjusting agent.The sintering aid is at least one of CuO, Bi2O3, B2O3, ZnO, TeO2, TiH2, Cu(HCOO)2 and CuC2O4.The conductive copper paste for microwave dielectric ceramic metallization, the preparation method and the application thereof are aimed at improving the oxidation resistance of the copper-based conductive paste and the adhesion between the copper-based conductive paste and the microwave dielectric ceramic, and realizing large-scale and low-cost manufacturing of microwave devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic materials technology, and in particular to a conductive copper paste for microwave dielectric ceramic metallization, its preparation method, and its application. Background Technology

[0002] Microwave dielectric ceramics, a novel functional electronic ceramic material used in the 300MHz to 300GHz frequency band, play a core dielectric role in radio frequency and microwave components such as filters, resonators, and antennas due to their excellent dielectric properties. In the manufacturing process of microwave devices, the metallization process on the ceramic surface is crucial, directly determining the conductivity of the electrodes and the overall reliability of the device.

[0003] Currently, surface metallization methods for microwave dielectric ceramics mainly include thick-film methods, electroplating methods, chemical etching deposition methods, and secondary metallization methods. Thick-film methods utilize metallization electrode materials such as nickel, silver, and gold, with silver paste being the most commonly used surface electrode material in the industry. Although silver paste possesses excellent conductivity and oxidation resistance, silver is a scarce and precious metal, and its high raw material cost significantly restricts the large-scale, low-cost manufacturing of microwave devices. Furthermore, silver paste carries the risk of electromigration under high-frequency environments, and after aging or salt spray testing, surface bulging, peeling, pinholes, and silver migration often occur, affecting the long-term stability of the device.

[0004] Given that copper's conductivity is similar to silver's, and its resources are abundant and inexpensive, using copper paste to replace silver paste has significant economic value and weather resistance advantages. However, despite the obvious advantages of copper paste, copper is easily oxidized at high temperatures, leading to insufficient reliability during high-temperature co-firing. Furthermore, the compatibility of copper paste with microwave dielectric ceramics, its adhesion after sintering, and its high-frequency conductivity stability have not yet been effectively resolved, becoming the main bottlenecks restricting its replacement of silver paste.

[0005] Therefore, developing a copper-based conductive paste that performs similarly to silver paste in the microwave band and has good oxidation resistance and adhesion is a technical challenge that urgently needs to be solved. Summary of the Invention

[0006] The main objective of this invention is to propose a conductive copper paste for metallization of microwave dielectric ceramics, its preparation method, and its application, aiming to improve the oxidation resistance of copper-based conductive pastes and their adhesion to microwave dielectric ceramics, thereby enabling large-scale, low-cost manufacturing of microwave devices.

[0007] To achieve the above objectives, this invention proposes a conductive copper paste for microwave dielectric ceramic metallization, the raw materials of which include conductive copper powder, modified glass powder, organic carrier, dispersant and sintering aid; The raw materials for the modified glass powder include glass matrix and Q-value regulator; At least one of the sintering aids CuO, Bi2O3, B2O3, ZnO, TeO2, TiH2, Cu(HCOO)2 and CuC2O4.

[0008] Preferably, in the modified glass powder, the amount of the Q-value regulator added is 2-10 wt%, and the Q-value regulator includes any one of α-alumina, magnesium olivine, zinc silicate, barium magnesium tantalate, and barium zinc tantalate.

[0009] Preferably, the modified glass powder includes modified Bi-B-Zn system glass powder, modified Bi-Cu-Si system glass powder, and modified Si-B-Zn system glass powder.

[0010] Preferably, the mixing ratio of the modified Bi-B-Zn system glass powder, the modified Bi-Cu-Si system glass powder, and the modified Si-B-Zn system glass powder by mass is (2-5):(1-2):(0.5-1). The modified glass powder has a particle size of 0.1–5 μm.

[0011] Preferably, the conductive copper powder includes micron-sized spheres, nano-sized spheres, and flake powder, and the mixing ratio of the micron-sized spheres, nano-sized spheres, and flake powder by mass is (7-12):(2-6):(1-4). The particle size of the micron-sized spherical powder is 0.5–5 μm; The particle size of the nanosphere powder is 50-500 nm; The diameter of the powder flakes is 1–5 μm.

[0012] Preferably, the raw materials for the conductive copper paste used for microwave dielectric ceramic metallization include 50-85 wt% conductive copper powder, 1-10 wt% modified glass powder, 10-40 wt% organic carrier, 0.1-3 wt% dispersant and 0.1-3 wt% sintering aid.

[0013] Preferably, the organic carrier includes a resin binder, a defoamer, an organic solvent, a film-forming aid, a plasticizer, and a thixotropic agent; The resin binder includes at least one of ethyl cellulose, acrylic resin, and polyvinyl butyral; The defoamer includes at least one of polyether-modified silicone, polymerized propylene oxide, and ethylene oxide; The organic solvent includes at least one of butylcarbiol, butylcarbiol acetate, terpineol, and diethylene glycol monooctyl ether; The film-forming aid is butyl carbityl ester; The plasticizer includes at least one of dibutyl phthalate, aliphatic diester, fatty acid ester, and phthalate. The thixotropic agent includes at least one of fumed silica, organobentonite, castor oil, and polyamide wax; According to the mass ratio, the mixing ratio of the resin binder, the defoamer, the organic solvent, the film-forming aid, the plasticizer and the thixotropic agent is (0.7~6):(0.1~0.8):(4~30):(1~10):(0.1~2):(0.1~1); The dispersant includes at least one of BYK2009 and DIG685.

[0014] A method for preparing conductive copper paste for microwave dielectric ceramic metallization, comprising the following steps: The glass base material and Q-value regulator are mixed and ground, then melted to obtain a melt, which is then water-quenched and dried. Finally, after ball milling, drying and sieving, modified glass powder is obtained. The organic carrier is obtained by mixing the raw materials of the organic carrier evenly. Conductive copper powder, modified glass powder, organic carrier, dispersant and sintering aid are mixed evenly, and after degassing and rolling through a three-roll mill, conductive copper paste is obtained.

[0015] An application of a conductive copper paste for metallizing microwave dielectric ceramics in the preparation of metallized microwave dielectric ceramics, comprising the following steps: Provide microwave dielectric ceramic substrates; Conductive copper paste is coated onto the surface of the substrate, and the coating is either printing or spraying. Pre-curing is carried out at a temperature of 120–150°C; The microwave dielectric ceramic is sintered under an inert gas atmosphere to complete the metallization process.

[0016] Preferably, the sintering curve of the sintering is as follows: The temperature is increased from room temperature to 600–700℃ at a rate of 25–30℃ / min. The temperature is increased from 600–700℃ to 800–850℃ at a rate of 15–20℃ / min. The temperature is increased from 800–850℃ to 900–1000℃ at a rate of 5–10℃ / min. Keep warm at 900–1000℃ for 5–30 minutes; The temperature is reduced from 900–1000℃ to 800–850℃ at a rate of 15–20℃ / min. The temperature is reduced from 800–850℃ to room temperature at a rate of 5–10℃ / min.

[0017] The technical solution of this invention introduces Q-value modified glass powder and sintering aids into the conductive copper paste raw material. On the one hand, the modified glass powder can soften and wet the substrate at high temperatures, promoting the formation of a high-density sintered copper film, and reducing signal loss by adjusting the dielectric constant matching degree, thereby improving the quality factor of microwave devices. On the other hand, the sintering aid not only lowers the sintering temperature and inhibits excessive grain growth, but its active components can also remove the oxide film on the copper surface in situ, improve interfacial wettability, and accelerate mass migration, promoting sufficient intergranular or intragranular bonding at the metal interface. Through their interconnected fluxing effect, the two not only significantly improve the density of the sintered copper film, but also significantly enhance the adhesion between the copper layer and the substrate.

[0018] The realization of the objective, functional characteristics and advantages of the present invention will be further explained in conjunction with the embodiments. Detailed Implementation

[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.

[0021] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the use of "and / or" or "and / or" throughout the text includes three parallel solutions. For example, "A and / or B" includes solution A, solution B, or a solution where both A and B are satisfied simultaneously. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.

[0022] Copper is highly susceptible to oxidation at high temperatures, resulting in insufficient reliability during high-temperature co-firing. Furthermore, the compatibility of copper paste with microwave dielectric ceramics, its adhesion after sintering, and its high-frequency conductivity stability have not yet been effectively addressed, becoming the main bottlenecks restricting its replacement of silver paste.

[0023] In order to improve the oxidation resistance of copper-based conductive paste and its adhesion to microwave dielectric ceramics, and to achieve large-scale low-cost manufacturing of microwave devices, the present invention proposes a conductive copper paste for metallization of microwave dielectric ceramics, the raw materials of which include conductive copper powder, modified glass powder, organic carrier, dispersant and sintering aid. The raw materials for the modified glass powder include glass matrix and Q-value regulator; At least one of the sintering aids CuO, Bi2O3, B2O3, ZnO, TeO2, TiH2, Cu(HCOO)2 and CuC2O4.

[0024] Specifically, the copper paste raw material in this scheme contains modified glass powder modified with a Q-value regulator and sintering aids. Glass powder, as the inorganic binder phase in the copper paste system, can achieve dense bonding between particles through melt flow during high-temperature sintering. However, during the high-temperature sintering process of preparing microwave dielectric ceramics, the copper layer obtained by sintering is prone to sintering voids and partial pores, thus affecting the quality factor of the metallized microwave dielectric ceramics. Therefore, to improve these defects, this scheme first uses a Q-value regulator to modify the glass powder, enabling the modified glass powder to soften and wet the substrate during sintering, promote sintering, and form a high-density sintered copper film, while also promoting the bonding between the paste and the ceramic matrix. Furthermore, the introduction of the Q-value regulator also helps to reduce signal transmission loss and improve the quality factor of microwave devices by adjusting the matching degree between the dielectric constant of the paste and the microwave dielectric ceramic substrate.

[0025] Furthermore, the sintering aids in the raw materials can lower the energy barrier required for atomic migration, thereby activating the sintering process at lower temperatures, reducing energy consumption, and inhibiting excessive grain growth. In addition, the active components in the aids can undergo reduction or displacement reactions with the oxide film formed by the oxidation of copper paste at high temperatures, removing the oxide layer that hinders atomic bonding in situ, while improving interfacial wettability. This provides a clean and highly active contact interface for the subsequent bonding of the copper layer and the substrate, and can also accelerate mass migration, effectively shorten the inter-particle atomic diffusion distance, increase diffusion flux, and ultimately promote sufficient intergranular or intragranular bonding at the metal interface, resulting in a high-density sintered body.

[0026] Finally, through the synergistic melting effect of sintering aids and modified glass powder, the density of the sintered copper film is effectively improved, the adhesion between the sintered copper layer and the substrate is enhanced, and the goal of achieving strong adhesion with virtually no decrease in copper film adhesion after surface treatment (chemical plating processes such as electroless silvering, electroless nickel-golding, OSP, and electroplating) is achieved.

[0027] To further clarify, the amount of the Q-value regulator added in the modified glass powder is 2-10 wt%, and the Q-value regulator includes any one of α-alumina, magnesium olivine, zinc silicate, barium magnesium tantalate, and barium zinc tantalate.

[0028] In order to effectively improve the quality factor of copper paste and meet the requirements for the metallization of microwave dielectric ceramics, this solution also optimizes the amount and type of Q-value modifier to be added.

[0029] Preferably, the amount of Q-value regulator added to the modified glass powder is 4 wt%.

[0030] It should be noted that α-alumina (α-Al₂O₃) has a Q×f value that can reach 300,000–1,000,000 GHz, while its dielectric loss tanδ in the X-band is <1×10⁻⁶. -4 It exhibits no phase transformation or decomposition during high-temperature sintering and does not react with copper. Magnesia olivine (Mg₂SiO₄) has a Q×f value of approximately 190,000 GHz, and its dielectric loss tanδ in the X-band is (1~2)×10⁻⁶. -5 (@10GHz), belonging to ultra-low loss silicate ceramics; it has a dense structure and chemical stability, is not reduced under nitrogen / weak reducing atmosphere, does not react with copper, and does not suffer performance degradation. Furthermore, its thermal expansion coefficient matches well with copper, reducing co-firing stress. Zinc silicate (Zn₂SiO₄, zinc silicosite), barium magnesium tantalate (BMT), and barium zinc tantalate (BZT) also possess high Q×f values ​​and moderate dielectric constants, and as modifiers, they can effectively reduce dielectric loss and improve Q value.

[0031] To further clarify, the modified glass powder includes modified Bi-B-Zn system glass powder, modified Bi-Cu-Si system glass powder, and modified Si-B-Zn system glass powder.

[0032] To better meet the stringent requirements of microwave dielectric ceramic metallization, this solution further selects the type of modified glass powder. By optimizing the binder phase, voids and oxygen vacancies in the sintered copper layer can be effectively suppressed, and the heterogeneous interface bonding can be optimized to reduce contact resistance and transmission loss. This significantly improves the conductivity of the copper layer, ensures high-quality transmission of microwave signals, and fully meets the stringent requirements of microwave dielectric ceramic metallization.

[0033] Specifically, the modified glass powder in this scheme is a blend of Bi-B-Zn, Bi-Cu-Si, and Si-B-Zn systems. Since the softening point and thermal expansion coefficient of each system glass powder are different, the adhesion of the sintered copper layer can be made to meet the requirements by adjusting the ratio between the components. At the same time, it is easy to adjust the thermal expansion coefficient of the copper paste to match the thermal expansion coefficient of the microwave dielectric ceramic substrate, so as to ensure that the copper layer will not have a harmful interfacial reaction with the substrate to generate a high-loss phase, thereby reducing the Q value.

[0034] It should be noted that the raw materials for modified Bi-B-Zn glass powder include Bi-B-Zn glass matrix and Q-value modifier. The modification of Bi-B-Zn glass powder with Q-value modifier, Bi-Cu-Si glass powder, and Si-B-Zn glass powder is similar. Furthermore, the Bi-B-Zn, Bi-Cu-Si, and Si-B-Zn systems are all commonly used lead-free, low-melting-point glass powder systems in the field of electronic pastes; therefore, the glass powder components of these systems will not be elaborated upon here.

[0035] To further explain, the mixing ratio of the modified Bi-B-Zn system glass powder, the modified Bi-Cu-Si system glass powder, and the modified Si-B-Zn system glass powder, by mass, is (2-5):(1-2):(0.5-1). The modified glass powder has a particle size of 0.1–5 μm.

[0036] In a preferred embodiment of this technical solution, the proportions of modified glass powders compounded from Bi-B-Zn, Bi-Cu-Si, and Si-B-Zn systems were selected to effectively ensure the firing of high-density copper films and to ensure that the sintered copper films meet the performance requirements of thick-film metallization products.

[0037] To further explain, the conductive copper powder includes micron-sized spheres, nano-sized spheres, and sheet powder, and the mixing ratio of the micron-sized spheres, nano-sized spheres, and sheet powder by mass is (7-12):(2-6):(1-4). The particle size of the micron-sized spherical powder is 0.5–5 μm; The particle size of the nanosphere powder is 50-500 nm; The diameter of the powder flakes is 1–5 μm.

[0038] In another preferred embodiment of this technical solution, the conductive copper powder is composed of micron-sized spherical powder, nano-sized spherical powder and flake powder in a certain proportion, which is beneficial for constructing a high-density conductive interconnect network, reducing the influence of high-frequency skin effect, reducing signal transmission loss, and improving the quality factor of sintered copper layer.

[0039] Specifically, after sintering, the sheet powder can form a more continuous layered structure, providing a better surface conductivity path and effectively reducing losses caused by the skin effect; the spherical powder filling the spaces between the sheet powder can effectively increase the packing density and reduce sintering shrinkage and porosity. In addition, the spherical powder is a composite of micron-sized copper powder and nano-sized copper powder. The nano-spherical powder can induce liquid phase sintering in advance, forming a sintering neck, making the sintered copper film more dense.

[0040] To further explain, the raw materials for the conductive copper paste used for microwave dielectric ceramic metallization include 50-85 wt% conductive copper powder, 1-10 wt% modified glass powder, 10-40 wt% organic carrier, 0.1-3 wt% dispersant and 0.1-3 wt% sintering aid.

[0041] In a preferred embodiment of this technical solution, by controlling the conductive copper powder content to be within the range of 50–85 wt%, a continuous and dense conductive network is ensured after the slurry solidifies, giving it excellent conductivity. Simultaneously, the addition of 1–10 wt% modified glass powder as an inorganic binder not only effectively improves the adhesion between the copper layer and the substrate but also wets the ceramic matrix during sintering, promoting densification. Furthermore, the introduction of 0.1–3 wt% sintering aid significantly reduces the sintering temperature of the copper slurry, avoiding high-temperature oxidation of the copper powder, and synergistically improves the bonding state between the copper layer and the ceramic interface with the modified glass powder. In addition, the rational ratio of organic carrier and dispersant ensures excellent printability and storage stability of the slurry, resulting in a final copper layer with low resistivity, high adhesion, and good oxidation resistance, meeting the stringent requirements of microwave dielectric ceramic devices for high-performance electrode materials.

[0042] To further explain, the organic carrier includes resin binders, defoamers, organic solvents, film-forming aids, plasticizers, and thixotropic agents; The resin binder includes at least one of ethyl cellulose, acrylic resin, and polyvinyl butyral; The defoamer includes at least one of polyether-modified silicone, polymerized propylene oxide, and ethylene oxide; The organic solvent includes at least one of butylcarbiol, butylcarbiol acetate, terpineol, and diethylene glycol monooctyl ether; The film-forming aid is butyl carbityl ester; The plasticizer includes at least one of dibutyl phthalate, aliphatic diester, fatty acid ester, and phthalate. The thixotropic agent includes at least one of fumed silica, organobentonite, castor oil, and polyamide wax; According to the mass ratio, the mixing ratio of the resin binder, the defoamer, the organic solvent, the film-forming aid, the plasticizer and the thixotropic agent is (0.7~6):(0.1~0.8):(4~30):(1~10):(0.1~2):(0.1~1); The dispersant includes at least one of BYK2009 and DIG685.

[0043] In a preferred embodiment of this technical solution, the synergistic formulation of resin binder, defoamer, organic solvent, film-forming aid, plasticizer, and thixotropic agent in the organic carrier effectively enhances the overall performance of the conductive copper paste. Specifically, the resin binder ensures a strong bond between the copper layer and the substrate; the defoamer and thixotropic agent synergistically improve the rheological properties and printability of the paste, preventing bubbles and sagging defects; and the film-forming aid and plasticizer effectively optimize the flexibility and density of the cured film, preventing cracking. This results in excellent printing precision, a smooth film surface, and good process stability in the copper paste.

[0044] Furthermore, among existing thick-film metallization solutions, printing processes offer advantages such as compact workflow, high yield, and environmental friendliness. However, for the metallization of through-holes, blind holes, and complex three-dimensional ceramic structures, spray-applied high-temperature sintering copper paste technology shows significant application potential. In the actual copper paste coating process, the proportions of various raw materials in the organic carrier can be adjusted according to the process requirements of printing / spraying; this is not limited in this case.

[0045] It should be noted that BYK2009 refers to a structured acrylic copolymer solution produced by BYK Chemicals in Germany, and TEGO 685 refers to a high molecular weight polymer produced by the German brand TEGO.

[0046] Furthermore, the technical solution of the present invention also proposes a method for preparing conductive copper paste for microwave dielectric ceramic metallization, which includes the following steps: The glass base material and Q-value regulator are mixed and ground, then melted to obtain a melt, which is then water-quenched and dried. Finally, after ball milling, drying and sieving, modified glass powder is obtained. The organic carrier is obtained by mixing the raw materials of the organic carrier evenly. Conductive copper powder, modified glass powder, organic carrier, dispersant and sintering aid are mixed evenly, and after degassing and rolling through a three-roll mill, conductive copper paste is obtained.

[0047] The conductive copper paste preparation method provided by this invention effectively improves the overall performance and process adaptability of the paste through the synergistic cooperation of each step. First, the glass matrix and Q-value regulator are co-ground and melted, then water-quenched, ball-milled, and sieved. This ensures the uniform distribution of the Q-value regulator within the glass and precisely controls the particle size of the modified glass powder, effectively adjusting the quality factor of the metallized layer obtained after copper paste sintering to meet the requirements of high-frequency applications. Second, the pre-preparation of the organic carrier ensures the full dissolution and dispersion of its internal components, providing a uniform medium for subsequent paste mixing. Finally, by mixing and degassing the conductive copper powder, modified glass powder, organic carrier, dispersant, and sintering aid, and then rolling the mixture using a three-roll mill, uniform dispersion and thorough grinding of each component are achieved. This effectively eliminates air bubbles and agglomerates within the paste, significantly improving the paste's fineness, printability, and sintering density.

[0048] The preparation method proposed in this scheme has a compact process and controllable operation, and can stably obtain conductive copper paste with good conductivity, adhesion and high Q value, which is suitable for industrial mass production.

[0049] Furthermore, the technical solution of the present invention also proposes an application of a conductive copper paste for metallizing microwave dielectric ceramics in the preparation of metallized microwave dielectric ceramics. Using the above-mentioned conductive copper paste for metallizing microwave dielectric ceramics includes the following steps: Provide microwave dielectric ceramic substrates; Conductive copper paste is coated onto the surface of the substrate, and the coating is either printing or spraying. Pre-curing is carried out at a temperature of 120–150°C; The microwave dielectric ceramic is sintered under an inert gas atmosphere to complete the metallization process.

[0050] The metallization preparation method for microwave dielectric ceramics provided by this invention firstly involves coating conductive copper paste onto the substrate surface using printing or spraying methods. This method is flexible and adaptable, meeting the coating requirements of ceramic substrates with different shapes. Secondly, pre-curing at 120–150°C effectively avoids film defects such as pinholes and bubbles caused by the rapid volatilization of organic carriers at high temperatures, ensuring the smoothness and density of the cured film and laying a good foundation for subsequent sintering. Finally, sintering under inert gas protection effectively prevents the oxidation of copper powder at high temperatures, ensuring the high conductivity and low resistivity of the metallized layer, while avoiding adverse reactions at the interface between the copper layer and the ceramic substrate, significantly improving adhesion and reliability.

[0051] The metallization preparation method proposed in this solution is simple to operate and cost-effective. Working synergistically with conductive copper paste, it can stably produce metallized microwave dielectric ceramic devices with high Q values, low losses, and excellent environmental adaptability, making it suitable for industrial mass production. Furthermore, the metallization preparation method is highly compatible with existing thick-film printing, spraying, and co-firing processes, requiring no major equipment modifications and exhibiting extremely high process compatibility.

[0052] In one specific embodiment, the microwave dielectric ceramic substrate is obtained by high-temperature sintering of any one or more of MgTiO3, CaTiO3, and TiO2 in the required molar amounts, with a relative permittivity of 4-60 and a quality factor of not less than 2000 GHz. Before coating with conductive copper paste, the microwave dielectric ceramic substrate can be subjected to ultrasonic-assisted alkaline washing (e.g., using a 5wt% NaOH solution) to remove oil film and dust, followed by spraying with deionized water, and finally air-drying at 100-150°C.

[0053] In another specific embodiment, when the coating method is printing, the coating thickness of the conductive copper paste is 10–20 μm; when the coating method is spraying, the coating thickness of the conductive copper paste is 3–15 μm, and it is pre-cured at 120°C for 20 min, or at 150°C for 10 min. Furthermore, if there is substrate leakage after a single spraying and sintering process, the spraying effect can be improved by multiple spraying and curing processes.

[0054] Preferably, the inert gas is nitrogen.

[0055] To further explain, the sintering curve is as follows: The temperature is increased from room temperature to 600–700℃ at a rate of 25–30℃ / min. The temperature is increased from 600–700℃ to 800–850℃ at a rate of 15–20℃ / min. The temperature is increased from 800–850℃ to 900–1000℃ at a rate of 5–10℃ / min. Keep warm at 900–1000℃ for 5–30 minutes; The temperature is reduced from 900–1000℃ to 800–850℃ at a rate of 15–20℃ / min. The temperature is reduced from 800–850℃ to room temperature at a rate of 5–10℃ / min.

[0056] In a preferred embodiment of this technical solution, the sintering curve of the sintering process is further optimized by sequentially using a stepped heating / cooling curve of rapid heating—medium-speed heating—slow heating—peak holding—rapid cooling—slow cooling to achieve effective sintering and interface bonding of copper particles and avoid oxidation and pore formation.

[0057] The present invention will be further illustrated below through specific embodiments: Example group 1. According to the raw materials and proportions in Table 1 below, mix the glass base material and Q-value regulator and then grind them; The ground material is added to a crucible, heated from room temperature to 1300℃ for 130 minutes, and then held at 1300℃ for 60 minutes to melt it. The melt is then water-quenched and dried at 150℃. 10mm zirconium beads, 1mm zirconium beads, dried material and water were mixed in a mass ratio of 1:1:1:1 and ball-milled at 350 rpm for 120 min. After drying, the mixture was passed through a 325-mesh sieve to obtain modified glass powder of 0.1-3μm, which includes modified Bi-B-Zn system glass powder, modified Bi-Cu-Si system glass powder and modified Si-B-Zn system glass powder.

[0058] 2. According to the proportions in Table 2 below, ethyl cellulose EC-N50, ethyl cellulose EC-N10, acrylic resin, polyether-modified organosilicon, terpineol, butyl carbolic acid, butyl carbitol, dibutyl phthalate, and polyamide wax are mixed evenly to obtain an organic carrier.

[0059] 3. According to the raw materials and proportions in Table 2 below, the conductive copper powder, modified glass powder, organic carrier, dispersant and sintering aid are mixed evenly. After degassing (using a degassing machine, the degassing process parameters are: 1200rpm degassing for 5min, 1500rpm degassing for 10min and 700rpm degassing for 5min) and rolling through a three-roll mill (roll gaps are 40μm, 20μm and 10μm respectively), conductive copper paste is obtained.

[0060] Comparative group 1. Grind the glass base material according to the raw materials and proportions in Table 1 below; The ground material is added to a crucible, heated from room temperature to 1300℃ for 130 minutes, and then held at 1300℃ for 60 minutes to melt it. The melt is then water-quenched and dried at 150℃. 10mm zirconium beads, 1mm zirconium beads, dried material and water were mixed in a mass ratio of 1:1:1:1 and ball-milled at 350 rpm for 120 min. After drying, the mixture was passed through a 325-mesh sieve to obtain glass powder with a particle size of 0.1–3 μm, which includes Bi-B-Zn system glass powder, Bi-Cu-Si system glass powder and Si-B-Zn system glass powder.

[0061] 2. According to the proportions in Table 3 below, ethyl cellulose EC-N50, ethyl cellulose EC-N10, acrylic resin, polyether-modified organosilicon, terpineol, butyl carbolic acid, butyl carbitol, dibutyl phthalate, and polyamide wax are mixed evenly to obtain an organic carrier.

[0062] 3. According to the raw materials and proportions in Table 3 below, the conductive copper powder, glass powder, organic carrier, dispersant and sintering aid are mixed evenly. After degassing (using a degassing machine, the degassing process parameters are: 1200rpm degassing for 5min, 1500rpm degassing for 10min and 700rpm degassing for 5min) and rolling through a three-roll mill (roll gaps are 40μm, 20μm and 10μm respectively), conductive copper paste is obtained.

[0063] Table 1

[0064] Table 2

[0065] Table 3

[0066] The appearance of the conductive copper paste prepared in the example group and the comparative group was observed, and the fineness of the conductive copper paste was tested using a scraper fineness meter. At the same time, the viscosity and thixotropic index of the conductive copper paste were tested using an Anton Paar MCR302 rheometer (rotor speed of 4 rpm, test at a constant temperature of 25℃). The results are shown in Table 4 below.

[0067] Table 4

[0068] Applications of conductive copper paste for metallization of microwave dielectric ceramics in the preparation of metallized microwave dielectric ceramics: A. The microwave dielectric ceramic substrate is subjected to ultrasonic-assisted alkaline washing using a 5wt% NaOH solution, followed by spraying with deionized water and air drying at 150℃. B. The conductive copper pastes prepared in the example group and the comparative example group are printed on the surface of the substrate, respectively. C. Pre-curing at 130℃; D. Sintering is carried out under a nitrogen atmosphere to complete the metallization of the microwave dielectric ceramic. The sintering curves are as follows: heating from room temperature to 620℃ at a rate of 27℃ / min; heating from 620℃ to 870℃ at a rate of 16.7℃ / min; heating from 870℃ to 940℃ at a rate of 9.3℃ / min; holding at 940℃ for 15 min; cooling from 940℃ to 810℃ at a rate of 17.3℃ / min; and cooling from 810℃ to room temperature at a rate of 8.7℃ / min.

[0069] The thickness, solderability, bonding strength, conductivity, roughness, and Q value (under 2.4 GHz conditions) of the conductive copper layer in the metallized microwave dielectric ceramic prepared above were tested according to the test methods described in GB / T 17473.1-GB / T 17473.7. The results are shown in Table 5 below.

[0070] Table 5

[0071] As can be seen from the performance test data in Table 5, the Q value (2.4GHz) of the example group reached over 2200, which is much higher than the Q value of the comparative group. This indicates that the conductive copper layer prepared in the examples has lower energy loss and better resonance performance in the microwave band, and can meet the stringent requirements of high Q value signal transmission in filters. Furthermore, the solderability, adhesion, conductivity, and roughness all meet the requirements of GB / T 17473.7-2022 Noble Metal Pastes for Microelectronics Technology.

[0072] The above description is merely an exemplary embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A conductive copper paste for microwave dielectric ceramic metallization, characterized in that, The raw materials include conductive copper powder, modified glass powder, organic carrier, dispersant, and sintering aid; The raw materials for the modified glass powder include glass matrix and Q-value regulator; At least one of the sintering aids CuO, Bi2O3, B2O3, ZnO, TeO2, TiH2, Cu(HCOO)2 and CuC2O4.

2. The conductive copper paste for microwave dielectric ceramic metallization as described in claim 1, characterized in that, In the modified glass powder, the amount of the Q-value regulator added is 2-10 wt%, and the Q-value regulator includes any one of α-alumina, magnesium olivine, zinc silicate, barium magnesium tantalate, and barium zinc tantalate.

3. The conductive copper paste for microwave dielectric ceramic metallization as described in claim 1, characterized in that, The modified glass powder includes modified Bi-B-Zn system glass powder, modified Bi-Cu-Si system glass powder, and modified Si-B-Zn system glass powder.

4. The conductive copper paste for microwave dielectric ceramic metallization as described in claim 3, characterized in that, According to the mass ratio, the mixing ratio of the modified Bi-B-Zn system glass powder, the modified Bi-Cu-Si system glass powder, and the modified Si-B-Zn system glass powder is (2~5):(1~2):(0.5~1). The modified glass powder has a particle size of 0.1–5 μm.

5. The conductive copper paste for microwave dielectric ceramic metallization as described in claim 1, characterized in that, The conductive copper powder includes micron-sized spheres, nano-sized spheres, and sheet powder, and the mixing ratio of the micron-sized spheres, nano-sized spheres, and sheet powder by mass is (7-12):(2-6):(1-4). The particle size of the micron-sized spherical powder is 0.5–5 μm; The particle size of the nanospheres is 50–500 nm; The diameter of the powder flakes is 1–5 μm.

6. The conductive copper paste for microwave dielectric ceramic metallization as described in claim 1, characterized in that, The raw materials include 50-85 wt% conductive copper powder, 1-10 wt% modified glass powder, 10-40 wt% organic carrier, 0.1-3 wt% dispersant and 0.1-3 wt% sintering aid.

7. The conductive copper paste for microwave dielectric ceramic metallization as described in claim 1, characterized in that, The organic carrier includes resin binder, defoamer, organic solvent, film-forming aid, plasticizer, and thixotropic agent; The resin binder includes at least one of ethyl cellulose, acrylic resin, and polyvinyl butyral; The defoamer includes at least one of polyether-modified silicone, polymerized propylene oxide, and ethylene oxide; The organic solvent includes at least one of butylcarbiol, butylcarbiol acetate, terpineol, and diethylene glycol monooctyl ether; The film-forming aid is butyl carbityl ester; The plasticizer includes at least one of dibutyl phthalate, aliphatic diester, fatty acid ester, and phthalate. The thixotropic agent includes at least one of fumed silica, organobentonite, castor oil, and polyamide wax; According to the mass ratio, the mixing ratio of the resin binder, the defoamer, the organic solvent, the film-forming aid, the plasticizer and the thixotropic agent is (0.7~6):(0.1~0.8):(4~30):(1~10):(0.1~2):(0.1~1); The dispersant includes at least one of BYK2009 and DIG685.

8. A method for preparing conductive copper paste for microwave dielectric ceramic metallization, characterized in that, The method for preparing conductive copper paste as described in any one of claims 1 to 7 comprises the following steps: The glass base material and Q-value regulator are mixed and ground, then melted to obtain a melt, which is then water-quenched and dried. Finally, after ball milling, drying and sieving, modified glass powder is obtained. The organic carrier is obtained by mixing the raw materials of the organic carrier evenly. Conductive copper powder, modified glass powder, organic carrier, dispersant and sintering aid are mixed evenly, and after degassing and rolling through a three-roll mill, conductive copper paste is obtained.

9. An application of a conductive copper paste for metallizing microwave dielectric ceramics in the preparation of metallized microwave dielectric ceramics, characterized in that, Using the conductive copper paste for microwave dielectric ceramic metallization as described in any one of claims 1 to 7, the method comprises the following steps: Provide microwave dielectric ceramic substrates; Conductive copper paste is coated onto the surface of the substrate, and the coating is either printing or spraying. Pre-curing is carried out at a temperature of 120–150°C; The microwave dielectric ceramic is sintered under an inert gas atmosphere to complete the metallization process.

10. The application as described in claim 9, characterized in that, The sintering curve of the sintering process is as follows: The temperature is increased from room temperature to 600–700℃ at a rate of 25–30℃ / min. The temperature is increased from 600–700℃ to 800–850℃ at a rate of 15–20℃ / min. The temperature is increased from 800–850℃ to 900–1000℃ at a rate of 5–10℃ / min. Keep warm at 900–1000℃ for 5–30 minutes; The temperature is reduced from 900–1000℃ to 800–850℃ at a rate of 15–20℃ / min. The temperature is reduced from 800–850℃ to room temperature at a rate of 5–10℃ / min.